PELANGGARAN PENCATATAN LAPORAN KEUANGAN OLEH PT. GARUDA INDONESIA - Keyzha Arta Nugraha; Ngafifatun Nurul Azizah; Maysandra Dwianzahra; Muthia Nurul Fadhilla; Ichtiar Hendra Satyadan; Brian Septiadi Daud (House of Management and Business (HOMBIS) Journal, 2023)
This research was conducted to find out the case that occurred at PT Garuda Indonesia. PT Garuda Indonesia decided to go public and issue its initial shares, meaning that PT Garuda Indonesia is listed on the Indonesia Stock Exchange and should present financial statements as one of the IPO companies in Indonesia. This attracted the attention of researchers to examine whether there were irregularities in the 2018 financial statements of PT Garuda Indonesia Tbk, which at that time was in the spotlight because the company's financial statements did not meet the requirements of the Financial Accounting Standards (PSAK). The method used by researchers in this study is the data analysis method using qualitative approaches.Keywords: Violation; Recording; Financial Statements